Prevalence and Molecular Characteristics of Klebsiella pneumoniae Harboring the Pks Island from Cancer Patients in China - Wang Q; Wang X; Xie Z; Qu J; Lin Y; Hu J; Li L; Zhang L (Infection and Drug Resistance, 2025)
Qun Wang,1 Xingwei Wang,2 Zhenghua Xie,1 Jiuxin Qu,2 Yongping Lin,1 Jing Hu,3 Liqiang Li,2 Li Zhang1 1National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital & Shenzhen Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Shenzhen, 518116, People’s Republic of China; 2Department of Clinical Laboratory, Shenzhen Third People’s Hospital, National Clinical Research Center for Infectious Diseases, The Second Affiliated Hospital of Southern University of Science and Technology, Shenzhen, Guangdong, People’s Republic of China; 3KingMed School of Laboratory Medicine, Guangzhou Medical University, Guangzhou, 510180, People’s Republic of ChinaCorrespondence: Li Zhang, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital & Shenzhen Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Shenzhen, 518116, People’s Republic of China, Email zldh33@163.com Liqiang Li, Department of Clinical Laboratory, Shenzhen Third People’s Hospital, National Clinical Research Center for Infectious Diseases, The Second Affiliated Hospital of Southern University of Science and Technology, Shenzhen, Guangdong, People’s Republic of China, Email jimmy198360@163.comPurpose: Klebsiella pneumoniae harbors a gene cluster, polyketide synthase island (PKS), which is responsible for colibactin synthesis which induces double-stranded DNA breaks and associated with increased pathogenicity and cancer development. However, there is limited information on pks-positive K. pneumoniae in cancer patients in China. This study aimed to investigate the prevalence and molecular characteristics of K. pneumoniae harboring the pks island in patients with cancer in China and to explore its potential pathogenicity and clinical significance.Methods: Among 279 nonrepetitive K. pneumoniae isolated from all cancer patients in China, the presence of pks genes were determined by PCR and the molecular characteristics were detected by whole-genome sequencing. Clinical characteristics and antimicrobial susceptibility were also investigated.Results: The pks gene cluster was detected in 35 (12.54%) of the 279 isolates. All isolates were less resistant to most antimicrobial agents, and there were no significant differences in the rates of susceptibility between pks-positive and pks-negative isolates to most antibiotics, except for sulfonamides. Among pks-positive isolates, ST23 (19, 54.29%) and K1 (17, 48.57%) were the dominant sequence types and serotypes, respectively, and the majority harbored multiple virulence genes, including aerobactin, enterobactin, salmochelin, and yersiniabactin.Conclusion: The distribution of pks-positive K. pneumoniae in different types of cancer combined with its hypervirulent determinants highlighted the potential pathogenicity of genotoxins, which requires close clinical attention and epidemic tracking.Keywords: PKS island, colibactin, Klebsiella pneumoniae, cancer, hypervirulent Klebsiella pneumoniae